1928
DOI: 10.1525/aa.1928.30.4.02a00040
|View full text |Cite
|
Sign up to set email alerts
|

Genna in Southeastern Asia

Abstract: and French Indo-China, is inhabited chiefly by peoples who belong to four linguistic stocks-the Tibeto-Burman, the Chinese, the Thai, and the Mon-Khmer. Of these, the first and last exhibit, in varying form and under diverse names, a social-religious complex, ordinarily called Genna by Englishspeaking writers.In the Tibeto-Burman group are included, from Burma, the Burmese, the Chin, and the Kachin, as well as their more northerly congeners, who, like the Moso and Lisu, occupy the borderlands between Yunnan, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…They gradually evolved an annual cycle of agricultural ceremonies, diverse sorts of sepulchral monuments in wood, phallic posts, and phallicism (Katz, 1928). Katz (1928) has counted about 200 situations/rites under the Genna and Kenna-Penna, as proclaimed by the shaman-priests. Within the genna complex, both "religious" and "social gennas" are recognized.…”
Section: Genna Conception In South East Asiamentioning
confidence: 99%
See 2 more Smart Citations
“…They gradually evolved an annual cycle of agricultural ceremonies, diverse sorts of sepulchral monuments in wood, phallic posts, and phallicism (Katz, 1928). Katz (1928) has counted about 200 situations/rites under the Genna and Kenna-Penna, as proclaimed by the shaman-priests. Within the genna complex, both "religious" and "social gennas" are recognized.…”
Section: Genna Conception In South East Asiamentioning
confidence: 99%
“…Writing in 1928, Katz observed that the numerous “tribes” belonging to Tibeto-Burman and the Mon-Khmer stocks spread in vast peninsula of South-Eastern Asia, including Burma as also Northeast (then called Assam) exhibit, in varying form and under diverse names, a social–religious complex, ordinarily called “Genna” (Katz, 1928). These tribes had advanced the notions of Penna and Kenna, and erected great stones, dolmen, and menhir in honor of their dead (1928).…”
Section: Genna Conception In South East Asiamentioning
confidence: 99%
See 1 more Smart Citation